Ferroptosis in Glioma Immune Microenvironment: Opportunity and Challenge - Wang, Kaikai; Wang, Junjie; Zhang, Jiahao; Zhang, Anke; Liu, Yibo; Zhou, Jingyi; Wang, Xiaoyu; Zhang, Jianmin (Frontiers in Oncology, 2022)
Glioma is the most common intracranial malignant tumor in adults, the 5-year survival rate of glioma patients is extremely poor even patients receive STUPP treatment after diagnosis, this forces us to explore more efficient clinical strategies. Nowadays, immunotherapy shows great potential in a variety of tumor clinical treatment, however, its clinical effect in glioma is limited because of tumor immune privilege which was induced by glioma immunosuppressive microenvironment, so remodeling immunosuppressive microenvironment is a practical way to eliminate glioma immunotherapy resistance. Recently increasing studies have confirmed that ferroptosis, a new form of cell death, plays an important role in tumor progression and immune microenvironment, and the crosstalk between ferroptosis and tumor immune microenvironment attracts lots of attentions. This work tends to summarize the progress studies of ferroptosis in glioma immune microenvironment.